Cross-Cultural Intelligibility and the Use of History: From Democracy and Liberalism to Indian Rajanical Thought. Issue 2 (14th April 2016) - Gray, Stuart
Abstract: While numerous methodological and interpretive challenges confront the study of cross-cultural political theory, this essay examines a particular premodern Indian tradition as an example of such difficulties and one way in which they can be overcome. Exploring the problematic ways in which people have interpreted and made use of India's ancient past, it critically examines arguments for the existence of secularism, free elections, and democratic assemblies in the Vedas. Defending what I call a "critical revivalist" position, it is argued that predominant approaches to premodern traditions in contemporary Indian political theory place significant constraints on cross-cultural intelligibility and theory building within the Indian context. To elaborate this point, I shift from a "political" to rājan-oriented categorical register in an effort to reposition current understandings of self-rule ( swaraj ) in India within a broader rajanical tradition. Finally, this essay explains how contemporary Indian political theory can draw insights from this native tradition without necessarily reverting to familiar Western idioms.